An empirical analysis of state fragility and growth: The impact of state ineffectiveness and political violence - Ines A. Ferreira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The role of the state in promoting development is well established in the institutional economics literature. Yet, in recent decades the attention has been turned to the opposite side of the spectrum. Facing high levels of poverty and showing a slower progress in achieving development outcomes, fragile states raised concerns among the development community, which felt urged to assist them. However, the quantitative empirical literature examining the link between state fragility and development is still relatively scanty. This paper sheds light on this issue by proposing an approach that comprises indicators for state ineffectiveness and political violence as two dimensions of state fragility, and by using data for the period 1993-2012 in order to understand their impact on growth. The results from standard econometric methods suggest that there is a significant negative effect of state ineffectiveness on economic growth, whereas they fail to find any significant impact of political violence.
Keywords: H11; O11; O43; 330; state fragility; state ineffectiveness; political violence; economic growth; OLS; IV